On Features of Greetings in Opening Sentence of Spiritual Letter (on Epistolary Heritage of Russian Monks of 20th Century) - A. N. Smolina (Научный диалог, 2017)
The peculiarities of etiquette speech genre of greeting in the Russian spiritual letter are covered. Referring to the epistolary heritage of Russian spiritual mentors-monks, the author shows that the greetings in the spiritual letters are significantly different from the greetings in the other types of private letters. The examples taken from texts that are addressed to the spiritual disciples, relatives, clergy, show that the differences relate mainly to etiquette formulas, and such formulas, as Christ is among us , Christ is risen , Save us, Lord , Save us, God and others became a marker of spiritual writing. Special attention is paid to the consideration of the causes of the distinctive features of the greetings in the letters of Russian monks. Conditionality of the existence of particular etiquette formulas is seen primarily in the Christian worldview of the correspondents, their following the traditions of Hesychasm and epistolary canons established by the Church writers of the past. The author also outlines the issues associated with the principle of theocentrism, which, as the analysis of religious epistolary texts shows, is reflected in their etiquette. The most frequent etiquette formulas used in the greetings are those that contains the words God , Christ , of God , Lord . The Christian idea of salvation determines the use of greeting words Save your soul , Be saved .